Identification of Anorthite-enriched Plagioclase Antecrysts in the Bushveld Complex, South Africa. (3rd May 2019) - Cawthorn, R Grant
Abstract: The origin of cumulate grains in layered intrusions is actively debated. Earliest views assumed that all grains grew in the now-exposed magma chamber. An alternative view is that some grains were injected from deeper magma chambers (never to be exposed). Such grains have been called antecrysts. In this model upward reversals in the anorthite content of plagioclase grains in anorthosite-bearing sequences have been considered to indicate such processes, and are considered to represent the bases of cycles. Data from two deep boreholes in the upper half of the Bushveld Complex permit testing of such ideas. Careful inspection shows that anorthosites (over 45 in one core and 12 in another) do not show an increase in their anorthite contents relative to their immediate footwall samples. Further, all examples of cycles (where enough closely spaced samples are available) in one borehole show that there is a slow upward increase in the anorthite contents over tens of metres and several samples, and that anorthosite does not occur at the base of such reversals, inconsistent with injection and accumulation of a slurry of grains with constant composition. Multiple analyses of many grains in a single sample show a typical standard deviation of ±1·5% An. However, a very few samples from both boreholes show a much larger standard deviation. Examination of every single analysis from one core shows that there are rare, isolated grains with a much higher anorthite content (±5%) than the average, rarely more than one per sample (out of 10–20 analyses). It is perfectly possible that these grains are indeed antecrysts. They are not located specifically in anorthosite samples, but can occur in rocks with any proportion of plagioclase. Based on 3000 analyses they constitute of the order of 1% of the total analysed population. The injection of magma may have occurred, but its entrainment of slurries of plagioclase is not consistent with these data.